Disutility of Cognitive Processing Speed (CPS) Impairment in the Context of Multiple Sclerosis: A Time Trade-Off (TTO) Elicitation Study - Benedict RH; Vo P; Adlard N; Grennan O; Enstone A; Bridge D; Wyn R; Cohan SL (Dove Medical Press, 2024)
Ralph HB Benedict,1 Pamela Vo,2 Nicholas Adlard,2 Olwyn Grennan,3 Ashley Enstone,4 Daisy Bridge,4 Robin Wyn,4 Stanley L Cohan5 1Department of Neurology, Jacobs School of Medicine and Biomedical Sciences, Buffalo, NY, USA; 2Novartis Pharma AG, Basel, Switzerland; 3Novartis Ireland, Dublin, Ireland; 4Adelphi Values PROVE, Bollington, UK; 5Providence Brain and Spine Institute, Providence St. Joseph Health, Portland, OR, USACorrespondence: Pamela Vo, Email pamela.vo@novartis.comIntroduction: Cognitive impairment, especially relating to cognitive processing speed, is a major cause of disability in people with multiple sclerosis (MS). Utility values are quantitative estimates of the quality of life experienced in specific health states and are a key component of cost-effectiveness modelling. However, existing health state utility values in MS typically focus on physical ability and are generally derived using generic (not disease-specific) measures of quality of life. The objective of the current study was to generate health state utility values for levels of cognitive impairment. We used a direct utility elicitation approach called the time trade-off (TTO) methodology.Materials and Methods: Health state descriptions were created following interviews with healthcare professionals, patients, and caregivers in the United States (n=35), and with healthcare professionals in the UK (n=5). Three health states (mild, moderate, and severe impairment) were defined based upon a well-established and validated test for cognitive dysfunction called the Symbol Digit Modalities Test (SDMT) and described using qualitative interview findings. Next, interviews with members of the general public in the UK were conducted to estimate utility values for each health state using the TTO methodology. The procedure was based on the established Measurement and Valuation of Health (MVH) protocol, which generates values on a scale from 0.0 to 1.0.Results: Mean health state utility values were 0.77 ± 0.24 in "mild impairment" (SDMT 43-40), 0.57 ± 0.26 in "moderate impairment" (SDMT 39-32), and 0.34 ± 0.28 in "severe impairment" (SDMT ≤ 31).Discussion: Results indicate that the public perceives that health states of cognitive slowing (as observed in MS) are associated with a substantial reduction in affected individuals' health-related quality of life, quantified using the TTO methodology. Future economic modeling should consider how utility impacts of both cognitive and physical disability can be appropriately incorporated.Keywords: cognitive impairment, processing speed, health state utility, health-related quality of life, multiple sclerosis, time trade-off